DAMPAK ONLINE SHOP TERHADAP PERILAKU KONSUMTIF MASYARAKAT MODERN di KOTA JAKARTA PUSAT - Kinanti; Maoliya Siti Nurfalida; Waisul Kurni Maulidi; Nur Eva Lestari; Salma Nurul Izzah; Oktavia Sholehah; Sena Agustin; Dianita Rahayu Sukmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Consumptive behavior is one of the most prominent elements in modern society. Consumptive behavior carried out by modern society in shopping activities via online shop platforms. The aim of this research is to find out the impact of online shops on consumer behavior in Central Jakarta City. The research method uses descriptive qualitative research using data collection methods such as, literature methods (Library Study), document review and interviews. Based on the results of interviews with several informants, it is known that the impact of online shops via e-commerce platforms has a great influence on the informants' consumptive behavior. This is also caused by the influence of social media which contains product advertisements with various promotional offers, so it is also known that some of these informants have fomo behavior. Apart from that, online shops also provide many conveniences to several informants because they are more time flexible, more comfortable because they can shop long distances so they prefer to buy products through online shops so they become consumptive.